Yacon flour (Smallanthus sonchifolius) to a symbiotic yogurt - Xavier, Milena Pimentel; Silva, Verônica Nicolini da; Pinheiro, Flávia; Rocha, Juliana; Spréa, Rafael Mascoloti; Amaral, Joana; Barros, Lillian; Freitas, Rosangela; Cardoso, Wilton (Food Science and Technology, 2025)
Adding functional ingredients to conventional products is an alternative to improve the population’s access to quality nutrition. In this sense, this work was conducted to transform traditional yogurt into a symbiotic product, through the incorporation of probiotic lactic bacteria and yacon flour, a potato rich in prebiotic fiber, inulin, and fructooligosaccharides. Yacon flour was produced and evaluated for its composition and prebiotic potential. Two concentrations of yacon flour with probiotic Bifidobacterium were evaluated. The yogurts were manufactured industrially in a dairy factory. The final yogurts were evaluated for their physicochemical, microbiological, and sensory characteristics. The yacon flour produced stood out for its concentration of 56% prebiotic fibers and high efficiency in promoting the growth of four different probiotic microorganisms. The yogurts, with the addition of 5.5 or 8% yacon flour, met all the physical and chemical standards established by law. In the probiotic activity, the minimum concentration of probiotic bacteria required was maintained within the shelf life. And in the sensory evaluation, the symbiotic yogurts with (5.5 and 8%) yacon were well evaluated regarding flavor; however, the texture and color aspects were not approved by the tasters, requiring some more tests to improve these characteristics.